BOTULINUM NEUROTOXIN (BONT/A) AS AN INDUCER OF ACUTE ANTERIOR UVEITIS IN HLA B27 PATIENTS : A LITERATURE REVIEW - Maharddhika Pambudy, Indra; Sitompul, Ratna; Distia Nora, Rina La; Veronica Mongan, Vionna Nadya (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background : HLA B27 related acute anterior uveitis is a chronic recurrent inflammation of uvea mainly in anterior chamber. The underlying mechanism seems to involves autoimmunity and autoinflammatory. Antigen has been proposed as a trigger, but its precise role is unclear. Aim : We systematically searched evidence for the involvement of antigen, including BoNT/A in triggering HLA-B27 associated disease. Methods : We searched four data base including Pubmed, Ebscohost, Sciencedirect, and Google Scholar. We also review the immunologic response to BoNT/A, its amino acid sequence, and homology with human protein Results: Eight studies reviewed which include the role of antigen in triggering uveitis. Four studies favour autoinflammatory pathway which involves B27 homodimer formation and its interaction with TH-17. Four studies favour autoimmunity pathway which involves molecular mimicry and activation of self reactive CD8+ T-Cells. All of which centralize the role of dendritic cells as antigen presenting cells. Five studies describe immune response to BoNT/A. BoNT/A capable of activating innate and immune system. Using BLAST program from NCBI, we found BoNT/A homology with cytokeratine 8. Conclusion : Two possible pathway on how antigen might trigger HLA B27 AAU. The first is through uveitogenic capacity of the antigen. The second mechanism is through homodimer formation. BoNT/A might induce uveitis in HLA B27 individual through induction of homodimer and activation of self-reactive CD8+ T-Cells due to shared homology with cytokeratine 8 that is extensively expressed in human uvea